Pengaruh Return On Asset (ROA), Return On Equity (ROE), Current Ratio (CR), Debt To Equity Ratio (DER), Dan Total Asset Turnover (TATO) Terhadap Kondisi Financial Distress (Studi Empiris Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bur - Yoyo, Toni; Agustinus Priyowidodo (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2024)
This study aims to examine the effect of return on assets, return on equity, current ratio, debt to equity ratio, and total asset turnover on financial distress conditions in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The independent variables used are return on asset (ROA), return on equity (ROE), current ratio (CR), debt to equity ratio (DER), and total asset turnover (TATO). The bound variable used is financial distress which is proxied by the Altman Z"-Score Method. The population of this study is food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The method used in this study is a quantitative method. The sampling technique uses a purposive sampling technique, with a total of 45 samples obtained from 9 companies for 5 years. The data used is secondary data, namely the annual financial statements of the sample companies for the 2019-2023 period. Data analysis techniques used descriptive statistical analysis, classical assumption test, multiple linear regression analysis, determination coefficient test, t-test, and F. Data processing was carried out using the SPSS (Statistical Product and Service Solutions) version 25 program. The results of this study prove that there is a significant influence of return on assets on financial distress, there is a significant influence of return on equity on financial distress, there is a significant influence of current ratio on financial distress, there is no significant influence of debt to equity ratio on financial distress, and there is no significant influence of total asset turnover on financial distress. The five independent variables (ROA, ROE, CR, DER, and TATO) simultaneously had a significant effect on financial distress.